L’espace dialogique chez Flaubert : la « cabane de l’Ermite » et le double pupitre des copistes - Rocky Penate (Flaubert: Revue Critique et Génétique)
This article deals primarily with the figuration of dialogue in La Tentation de saint Antoine and in Bouvard et Pécuchet, two novels in which it cannot be reduced to the textually related exchange of words. These are two works whose aesthetic and meaning rest on the idea of dialogue. While Antoine addresses himself to God, Bouvard and Pécuchet speak with one another. While the two copyists sustain a long dialogue with the authors that fill their library, until finally returning to their original profession, the saint conjures an entire catalogue of pagan gods and heretical voices before finally returning to his unequivocal prayers. That is to say that Antoine’s prayers are fundamentally reflexive, despite their apparent variety — they do not transcend the logic of the monologue. Bouvard and Pécuchet’s experience, on the other hand, proceed from a spirit of dialogue. At the end of their encyclopaedic wandering, they do not take up the same copying from which they have retired, but rather a sort of quoting that permits them to conserve their social bond — and a dialogue with the world free of cynicism.